Compositional Variations in Wheat Bran Influence Growth Performance, Nutrient Retention, and Cecal Microbiome in Broilers - Yujing Feng; Songjun Jiao; Ying Zhang; Youyou Liu; Feng Zhao; Yuming Wang; Renna Sa; Jingjing Xie (Animals)
Recent studies have discovered that wheat bran could stimulate digestive tract development, modulate intestinal microbiota, and improve the digestibility of fibrous ingredients in broilers. Wheat bran varies greatly in its chemical constituents. The objective of this study is to investigate how different types of wheat bran influence growth performance, nutrient digestion, and gut health in broiler chickens. Eight types of wheat bran were sampled and analyzed for nine constituents. A principal component analysis demonstrated that the wheat bran could be clustered into three groups based on the first principal component, namely low-fiber (LF), medium-fiber (MF), and high-fiber (HF) wheat bran. Wheat bran from the LF, MF, and HF groups significantly differed in terms of the contents of NDF, acid detergent fiber (ADF), hemicellulose, in vitro digestible energy (IVDE), crude fat, and ash (p < 0.05). A total of 324 seven-day-old broiler chicks were grouped into six body weight blocks. Each block of birds was randomly divided into six treatments, fed either a corn–soybean meal basal diet or five experimental diets, including 3% wheat bran from the LF, MF, and HF groups, until d 21. The feed/gain ratio was increased, and the coefficients of dry matter (DM, p = 0.001), gross energy (GE, p = 0.005) digestion, energy (p = 0.039), and CP (p = 0.051) retention were reduced in the birds that were fed 3% HF wheat bran. In contrast, in the birds fed 3% LF wheat bran, the coefficients of nutrient digestion and retention of energy and CP were not affected, but the CP (p = 0.009) and the NDF (p = 0.059) digestion ability were increased when switched to the same diet. In the cecal digesta, Barnesiella was enriched in the birds from the LF group, while Lachnospiracea was enriched in the birds from the MF group. Adding a moderate amount of wheat bran from the LF group could promote protein and fiber digestion and increase the abundance of Barnesiella in broilers.